2016
DOI: 10.1155/2016/2957151
|View full text |Cite
|
Sign up to set email alerts
|

A New Integrated Approach for the Prediction of the Load Independent Power Losses of Gears: Development of a Mesh-Handling Algorithm to Reduce the CFD Simulation Time

Abstract: To improve the efficiency of geared transmissions, prediction models are required. Literature provides only simplified models that often do not take into account the influence of many parameters on the power losses. Recently some works based on CFD simulations have been presented. The drawback of this technique is the time demand needed for the computation. In this work a less time-consuming numerical calculation method based on some specific mesh-handling techniques was extensively applied. With this approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…Small cells were inevitably produced and this causes a significant increment in the computational effort required, not so much for the increased number of elements, but for the need, in order to ensure the stability of the solution, to reduce drastically the time step (to keep the Co number equal to 1). The authors have shown how, with the so called global remeshing approach (GRA) [45], it is possible to have a much higher control of the grid parameters, ensuring huge time savings for the computation thanks to the bigger possible time steps.…”
Section: Fv Approachmentioning
confidence: 99%
“…Small cells were inevitably produced and this causes a significant increment in the computational effort required, not so much for the increased number of elements, but for the need, in order to ensure the stability of the solution, to reduce drastically the time step (to keep the Co number equal to 1). The authors have shown how, with the so called global remeshing approach (GRA) [45], it is possible to have a much higher control of the grid parameters, ensuring huge time savings for the computation thanks to the bigger possible time steps.…”
Section: Fv Approachmentioning
confidence: 99%
“…In presence of small gaps [18], and specifically between the valve and the valve seat, the size of the mesh results significantly reduced and the computational time increases significantly. Some specific techniques can be applied when the viscous contribution can be neglected [19], [20], but this is not the case. Despite of the symmetry, more than 2 million cells are required in order to properly discretize the domain.…”
Section: Performance Enhancementsmentioning
confidence: 99%
“…The amount of lubricant that ensures the proper lubrication of all the components has for a long time been selected empirically or by trial and error procedures, with the goal of minimizing the power losses . In recent years, the authors have demonstrated the effectiveness of the numerical computational fluid dynamic (CFD) approach in order to improve the efficiency of gearboxes, thanks to the possibility of optimizing the internal geometry and the lubricant level, on the basis of quantitative data and not only of experience …”
Section: Introductionmentioning
confidence: 99%
“…12 In recent years, the authors have demonstrated the effectiveness of the numerical computational fluid dynamic (CFD) approach in order to improve the efficiency of gearboxes, thanks to the possibility of optimizing the internal geometry and the lubricant level, on the basis of quantitative data and not only of experience. 13 In this paper, a recently developed simulation tool capable to take into account the effect of cavitation 14 is systematically applied to study the effect of the static depressurization on the load independent power losses of gears. Different static pressures and rotational speeds have considered.…”
Section: Introductionmentioning
confidence: 99%